Efeito do protetor solar sobre a fadiga durante a corrida com exposição ao sol - Kenya Paula Moreira Oliveira (2009)
Sunscreens may be water and sweat resistant, but it is unknown if they affect the production, secretion and evaporation of sweat and, hence, impair human thermoregulation. During prolonged or mild duration exercises, mainly those carried out in hot environments, thermoregulation plays a key role in the development of fatigue. If sunscreens indeed interfere with thermoregulatory mechanisms, then one would expect changes in fatigue. According to our literature review, this hypothesis has not been tested yet. Therefore, this study aims to evaluate the effect of two different types of sunscreen on fatigue during running in hot environments with sun exposure. Twelve voluntaries (six males and six females) gave their written consent to participate. A self-pace interval exercise protocol was applied and the voluntaries performed five 2 km-sessions with a 5-minute passive recovery between the sessions. Three experimental trials were carried out: a control without sunscreen (CON), one with a lotion sunscreen (SC1) and another with a cream sunscreen (SC2). Voluntaries were tested in groups of three, in the same environment, so that each of the subjects in a group was evaluated for one of the trials mentioned above. Measurements included running velocity, whole and local sweat rate, number of activated sweat glands, heart rate, rating of perceived exertion, thermal comfort, hydration status, physiological stress index, rate of heat storage and energy expenditure. Environmental conditions (temperature, thermal stress, relative humidity, wind velocity and luminosity) were monitored during the trials. Parametric variables were analyzed using ANOVA two-way or three-way with repeated measures (p < 0.05). Non parametrical variables were analyzed by Wilcoxon test (p < 0.05). The results showed no differences among the trials. Compared to males, females presented a larger number of activated sweat glands per cm2 and smaller running velocity, whole and local sweat rates, skin temperature, thermal comfort and energy expenditure. In this study, sunscreen application had no interference with performance or physiological and behavioral variables.